Networks of Pots: The Usage of Ceramics in Network Analysis in Mediterranean Archaeology - Daems Dries (Open Archaeology)
Pottery studies constitute a core domain in archaeology. The establishment of typo-chronologies forms the backbone of most chronological inferences in Mediterranean archaeology in particular. Computational approaches such as network science can help us expand the interpretative and explanatory power of these material frameworks in our understanding of the past. Network science has increasingly become mainstream in archaeology, yet, its applications in Mediterranean archaeology remain uneven and highly differential in scope and depth. In this article, I explore the potential and limitations of network science using three case studies of network analysis from Mediterranean archaeology. Each case study relates to a different research specialization and covers a different time period. I then show some of the potential of network analysis for pottery studies using an example from my own research on late Hellenistic and early Roman pottery from the eastern Mediterranean. This article outlines a way forward in which material specialists closely collaborate with other specialists such as computer scientists to develop new forms of synergy between computational methods and domain knowledge that can lift research outcomes to a higher level.